Update on the pathogenesis and treatment of childhood-onset systemic lupus erythematosus. Issue 5 (September 2016) - Couture, Julie; Silverman, Earl D.
Abstract : Purpose of review: This article will provide an update of studies published in the last year regarding epidemiology, pathogenesis, major disease manifestations and outcomes, and therapies in childhood-onset systemic lupus erythematosus (cSLE). Recent findings: Recent studies on cSLE epidemiology supported previous findings that cSLE patients have more severe disease and tend to accumulate damage rapidly. Lupus nephritis remains frequent and is still a significant cause of morbidity and mortality. In the past year unfortunately there were no new reproducible, biomarker studies to help direct therapy of renal disease. However, some progress was made in neuropsychiatric disease assessment, with a new and promising automated test to screen for cognitive dysfunction reported. There were no prospective interventional treatment trials designed for patients with cSLE published in the last year, but some studies involving children are currently active and might improve the therapeutic options for patients with cSLE. Summary: There is a need to get a better understanding of pathogenesis and identify new biomarkers in cSLE to more accurately predict outcomes. New insights into characterization of different clinical manifestations may enable to optimize individual interventions and influence the prognosis.